Efficacy of posaconazole prophylaxis in acute myeloid leukemia and myelodysplastic syndrome patients treated with hypomethylating agents. (October 2020) - Kang, Ka-Won; Lee, Byung-Hyun; Jeon, Min Ji; Yu, Eun Sang; Sik Kim, Dae; Lee, Se Ryeon; Sung, Hwa Jung; Choi, Chul Won; Park, Yong; Kim, Byung Soo
Background: Although many acute myeloid leukemia (AML) and myelodysplastic syndrome (MDS) patients have been treated with hypomethylating agents (HMAs) as a substitute for intensive chemotherapy in recent years, the incidence of invasive fungal infections (IFIs) and the efficacy of posaconazole as antifungal prophylaxis in these patients are not well known to date. Methods: We retrospectively analyzed 280 AML and MDS patients treated with HMAs to identify IFI incidence and posaconazole efficacy as antifungal prophylaxis in these patients. Results: The overall incidence of probable or proven IFIs was 7.9% (22/280 patients): 11.5% in the no-use group (17/148 patients) and 3.8% in the posaconazole group (5/132 patients). Most IFIs occurred during the early cycles of the HMAs (median: 3 cycles; range: 1–8 cycles), especially in patients who had neutropenia or did not respond to HMAs. Posaconazole significantly lowered IFI incidence compared with that in the no-use group in univariate and multivariate analyses. Moreover, patients who had reduced liver function at HMA initiation, were treated with decitabine therapy, and did not respond to HMA chemotherapy were independently associated with a higher IFI risk. In subgroup analysis, posaconazole appeared to be more beneficial for patients with good Eastern Cooperative Oncology Group performance score or liver function at HMA initiation. Conclusion: Thus, in AML and MDS patients receiving HMAs, IFI risk may be high during the early cycles, especially when the underlying disease is not controlled. Posaconazole could represent antifungal prophylaxis in these patients; further studies are needed for its appropriate indications.